Influence of Sample Preparation and Extraction Time on Chemical Composition of Steam Distillation Derived Patchouli Oil - Asdarina, Yahya; R. M., Yunus (Elsevier Ltd, 2013)
Patchouli or Pogostemon Cablin (Blanco) Benth is one of the species of essential oil plant. In Malaysia, patchouli is commonly known as’nilam’. It is widely appreciated because of its value in medicine, toiletries, perfumery and insecticides. Aromatic oils and their compounds have very good demand in national and international markets. In order to gain the optimum production from patchouli oil yield and quality, the best selection of sample preparation must be identified to prevent the chemical composition in the aromatic oils. This study investigates the effect of sample preparation on the yield and quality of patchouli oil, namely the chemical composition. Three different size of sample was prepared. Dried Patchouli plant (Pogostemon Cablin Benth) with an average length of 10-20 cm, 2-4 cm and 0-4 mm was used as the sample in the study. The production of patchouli oil can be obtained using steam distillation. The yield extracted from patchouli plant was collected every 2 hour until 10 hours of extraction time. This study examined the chemical composition of patchouli oil as a function of extraction time during steam distillation. Capillary gas chromatography - mass spectrophotometer (GC-MS) was used to determine the chemical composition of the extracted essential oil. The major composition to determine the patchou oil are β-patchoulene, α-guaiene, α-patchoulene, Patchouli alcohol, and α-bulnesene. The chemical percentage increased gradually with time up till 10 hours, in which exceeding this duration no increase in the yield was observed. Patchouli alcohol, the major component and characterized the patchouli oil, accounted for 47% in the extracted oil, from grind sample which complies with the commercial grade patchouli oil, 30%.